KawalPilpres2019: a highly secured real count voting escort architecture - Onno W. Purbo; Gildas Deograt; Rolof Satriyanto; Abraham Ferdinand; Pamadi Gesang; Rendra Kesuma; Kalpin Erlangga Silaen (Universitas Ahmad Dahlan, 2019)
This paper reports on the highly secured information security architecture used by the KawalPilpres 2019 to escort Voting Commission (KPU) data entry. For the first time, a voting escort implements ISO 27001 compliance information security. As of 15 May 2019, 9550 volunteers reported 482,602 voting data of 336,445 voting booths, both in the country and overseas, through the micro-apps KawalPilpres2019. PeSanKita is used as a secure communication channel and to run micro-apps KawalPilpres2019. Double Ratchet Algorithm secures the channel. Different from other voting escort initiatives, KawalPilpres2019 uses (1) primarily C1 Plano photo, (2) no upload limit per voting booth, (3) no web upload, rather via PeSanKita Secured Platform. Behind the scenes, the verification process is done twice before displaying data to the publicly accessible monitoring web. The result is a robust voting escort system, difficult to hack and guarantee data integrity. Guaranteed security, availability, and data integrity are the main requirements for future eVoting systems.